Performance Management and Employee Performance In Public Primary Teacher Training Colleges In Kenya - Miriti, Justine Majau (UoEm, 2024)
ABSTRACT The Kenyan government has adopted several major management reforms, one of which is the implementation of performance evaluation in public institutions, such as Public Primary Teacher Training Colleges (PPTTCs). The study sought to determine the impact of performance evaluation on staff output in PPTTCs in Kenya. Research using a descriptive methodology was used in this study. Convenience, purposive and stratified random sampling techniques were used to get the data. Including 1233 tutors, 189 department heads, 351 subject heads, 27 principals, 27 deputy principals, 27 curriculum deans and 27 deans of students, the target population consisted of 1881 appraised personnel from Kenyan PPTTCs. The sample size of 216 tutors, 33 department heads, 62 subject heads, 5 principals, 5 deputy principals, 5 curriculum deans and 5 student deans was calculated using Yamane's formula. Likert-scale questionnaires with five points were used to collect data in an organized format. The content validity was established through consulting with specialists in educational management. Cronbach's alpha was employed in order to assess the instrument dependability. Regression analysis was used to get the coefficient of the effect of performance evaluations on employee performance. Performance appraisal (PA) targets and worker production for Kenya's PPTTCs showed a weak connection (P-value = -0.016) in the study. As a result, increasing PA objectives might not be sufficient to enhance PPTTC employee performance. Organizational culture, leadership and employee motivation are a few other factors that might be more crucial. The coefficient of social distance between appraisers and appraisees was found to be 0.041. This indicates that an increase of one unit in social distance is expected to result in a 0.041 unit increase in employee performance. The results suggest that there may not be a strong correlation between social distance and employee performance. Specifically, the relationship between social distance and employee performance between appraisers and appraisees was found to be a weak predictor of employee performance (P=0.266). There's a chance that other elements like motivation, job-related abilities and company culture will affect performance more. P-value (0.687) related to employee performance in Kenya's PPTTCs did not show that PA training was a significant predictor of performance at the 0.05 level of statistical significance. This suggests that improving performance in PPTTCs may not always result from staff training on performance reviews. Furthermore, the research findings indicate that there is no significant correlation between job motivation and an employee's performance (P-value = 0.888 > 0.05). Employee training on PA had no discernible impact on workers' performance after accounting for the assessment scale (P-value = 0.687 > 0.05). According to the study, there is a substantial correlation (P-value=0.000) between employee performance and feedback from college performance reviews. The survey also found that performance goals are the most often used performance indicator and that, in order to guarantee that the evaluation process is successful in raising employee performance, PPTTCs should create specific, quantifiable goals. The study came to the conclusion that raising PA targets alone is not as effective in enhancing employee performance in PPTTCs as characteristics like organizational culture, leadership and employee motivation. The study also emphasizes how crucial performance review feedback is in affecting workers' output. Consequently, the study suggests that PPTTCs reconsider the structure and methodology of PA training programs while giving priority to improving organizational culture, leadership and feedback mechanisms within their PA systems.